Metal–organic framework composites with luminescent gold(iii) complexes. Strongly emissive and long-lived excited states in open air and photo-catalysis. Issue 12 (21st September 2015) - Sun, Chun-Yi; To, Wai-Pong; Wang, Xin-Long; Chan, Kaai-Tung; Su, Zhong-Min; Che, Chi-Ming
Abstract : Encapsulation of luminescent gold(iii ) complexes by metal–organic frameworks results in enhanced phosphorescence in open air, solid state two-photon-induced phosphorescence, and reusable photo-catalysts under aerobic conditions. Abstract : The encapsulation of luminescent gold(iii ) complexes by metal–organic frameworks (MOFs) lays the groundwork for new phosphorescent materials with activities that are not readily achieved by the host MOF materials or gold(iii ) complexes alone. In this work, strong phosphorescence with lifetimes of up to ∼50 μs in open air at room temperature has been achieved by incorporation of cationic cyclometalated gold(iii ) complexes into MOFs with anionic frameworks to form Au III @MOFs. The Au III @MOFs display solid state two-photon-induced phosphorescence. Photo-reduction of methyl viologen to the reduced radical was achieved inside Au III @MOFs and in the presence of Et3 N upon excitation at λ > 370 nm under ambient conditions. These Au III @MOFs comprise a class of reusable and size-selective heterogeneous photo-catalysts for the aerobic oxidation of secondary amines to imines as well as five other reactions, including oxidative C–H functionalization under aerobic conditions.